174 Forage Production and Nutritive Value of Alfalfa-bermudagrass Mixtures Managed Under Contrasting Defoliation Strategies in the Southeast US. (8th October 2021) - da Silva, Liliane Severino; Burt, Justin C; Mullenix, Mary K; Tucker, Jennifer J
Abstract: Incorporation of alfalfa (Medicago sativa) into bermudagrass pastures improves forage quality and decreases the reliance on synthetic nitrogen fertilizer. The objective of this study was to determine forage mass (FM), nutritive value (NV), and botanical composition of 'Bulldog 805' alfalfa and 'Tifton 85' bermudagrass (T85; Cynodon dactylon) mixtures managed under three defoliation strategies: 1) hay production (H), 2) grazing (G) or 3) dual-purpose (DP) use. The study was conducted in two locations (Headland, AL and Tifton, GA) using a randomized complete block design with two replicates. In spring 2020, grazed plots were divided in four strips and every 7-d, animals were rotated to a new strip and stocking rate was adjusted. Under DP, plots were grazed until mid-July, then forage was harvested in late August. For H plots, forage was harvested every 28 to 35-d. Forage samples were collected prior defoliation to determine FM and on grazed periods, pre- and post-grazing samples and disk meter measurements were collected. Nutritive value responses were determined using near-infrared spectroscopy. There was no effect of defoliation strategy on FM (P = 0.604; mean 3471 kg DM/ha). Greater FM (P = 0.002) was observed in July and August than June (3531 and 3976 vs 2905 kg DM ha-1, SE= 263). This response was associated with an up to 40% increase of T85 proportion in the mixture (P = 0.001). Alfalfa percentage was 78% greater for DP than G (P = 0.029). There were no differences among treatments for NV responses (P > 0.05). Among defoliation periods, crude protein, neutral detergent fiber and acid detergent fiber concentrations ranged from 14 to 22%, 45 to 58% and 28 to 35%, respectively. These preliminary results demonstrate multi-use options for this mixture in the region while aiming for increased forage nutritive value, and extended growing season, and sustainability of forage-livestock systems.